1994
DOI: 10.3109/00365549409008610
|View full text |Cite
|
Sign up to set email alerts
|

Age Specific Prevalence of Antibodies against Chlamydia pneumoniae in Iceland

Abstract: Chlamydia pneumoniae is a newly recognized common cause of respiratory tract infections. The aim of this study was to examine its prevalence in Iceland. The study was based on 1020 serum samples from individuals 0-99 years old. The samples were divided into 10-year age groups. IgG and IgM antibodies were determined with microimmunofluorescence assay. An IgG titer > or = 32 and IgM titer > or = 16 were considered positive. The prevalence of positive IgG titer in the study population was 53 +/- 16% (mean +/- SD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 17 publications
3
10
0
2
Order By: Relevance
“…This is in keeping with reports from other countries that C. pneumoniae seropositivity increases with age [14, 15, 16], with a 50–70% prevalence of seropositivity in middle-aged adults [23]. In contrast, a few studies report declining C. pneumoniae IgG titres with age [24, 25]. Most adults are infected two to three times during their lifetime [23], and increasing seropositivity with age is suggestive of chronic infection or reinfection throughout life.…”
Section: Discussionsupporting
confidence: 90%
“…This is in keeping with reports from other countries that C. pneumoniae seropositivity increases with age [14, 15, 16], with a 50–70% prevalence of seropositivity in middle-aged adults [23]. In contrast, a few studies report declining C. pneumoniae IgG titres with age [24, 25]. Most adults are infected two to three times during their lifetime [23], and increasing seropositivity with age is suggestive of chronic infection or reinfection throughout life.…”
Section: Discussionsupporting
confidence: 90%
“…Age-related seropositivity suggests that systemic C. pneumoniae may be relatively or wholly nontransmissible. Seropositivity is very low among children who have not yet attended school, rises steeply during the next three decades of life, and then levels off in older age groups, who remain predominantly seropositive [38][39][40][41][42]. About one-third of the adults who are in the typical age range of parents of such children (e.g., 25-35 years old) have some atherosclerotic damage [43].…”
Section: Evolution Of Antibiotic Resistancementioning
confidence: 99%
“…C. pneumoniae has been detected in numerous studies by various techniques in atheromatous plaques. Successful recovery of viable organisms from atherosclerotic lesions has also been reported (Einarsson et al 1994; Ramirez 1996).…”
Section: Introductionmentioning
confidence: 96%
“…C. pneumoniae is an obligate intracellular bacterial pathogen and a significant cause of respiratory tract infections in humans. Approx‐imately 10% of cases of community‐acquired pneumonia are associated with C. pneumoniae (Steinhoff et al 1996) and its prevalence rises with age (Einarsson et al 1994). In addition, seroepidemiological studies have shown an association between the antibody response to the organism and atherosclerosis (Saikku et al 1988).…”
Section: Introductionmentioning
confidence: 99%